Controllable fabrication of α-Ni(OH)2 thin films with preheating treatment for long-term stable electrochromic and energy storage applications. Issue 9 (31st January 2020) - Su, Chunhua; Qiu, Meijia; An, Yipeng; Sun, Siyuan; Zhao, Chuanxi; Mai, Wenjie
Abstract : Long-term stable, fast switching α-Ni(OH)2 electrodes for electrochromic energy storage application has been fabricated by one-step preheating treatment. The cost-effective fabrication is expected to expand to other metal hydroxide materials. Abstract : Although dual-functional electrochromic energy storage (EES) materials are important for the development of smart windows for energy-saving applications, few EES materials simultaneously possess fast switching time, long-term stability and high capacitance, which are among the most important characteristics for their applications. Herein, we present the controllable synthesis of pure α-Ni(OH)2 via an improved one-step electrodeposition process. The as-deposited Ni(OH)2 EES electrodes exhibited significantly enhanced performances with broad-range optical modulation of 78.6% at 550 nm, fast switching time of 0.9 s for coloration and 1.2 s for bleaching, as well as excellent stability (>5000 cycles). Meanwhile, the EES electrodes exhibited an excellent energy storage performance with an areal capacitance of 154.05 mF cm −2, and could light up a green light-emitting diode for 20 min. The improved EES performance is mainly attributed to the phase-controllable fabrication of uniform and compact α-Ni(OH)2 thin films with a small charge-transfer resistance, which exhibit a stable structure, allowing for fast ion intercalation/de-intercalation during the reversible redox reactions. The scalable and cost-effective fabrication of α-Ni(OH)2 materials is expected to expand the EES applications to other metal hydroxide materials.